2020
DOI: 10.1002/ece3.6217
|View full text |Cite
|
Sign up to set email alerts
|

Climatic variables influence the temporal dynamics of an anuran metacommunity in a nonstationary way

Abstract: Understanding the temporal dynamics of communities is crucial to predict how communities respond to climate change. Several factors can promote variation in phenology among species, including tracking of seasonal resources, adaptive responses to other species, demographic stochasticity, and physiological constraints. The activities of ectothermic vertebrates are sensitive to climatic variations due to the effect of temperature and humidity on species physiology. However, most studies on temporal dynamics have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 71 publications
3
2
0
Order By: Relevance
“…This is consistent with previous Mediterranean ecosystem assessment studies, and results that identified macroinvertebrate diversity as contributing disproportionately to ecological knowledge for the North African region (Beauchard et al, 2003;Ball et al, 2013;De Figueroa et al, 2013;Slimani et al, 2019). Benthic macroinvertebrates depend on a wide range of abiotic factors, including climate, water physiochemistry, anthropogenic pressures and riparian habitat availability (White et al, 2019;Ceron et al, 2020) and this study confirms that this is also true for aquatic insects such as Heteroptera. This study also supports the finding of research linking the distribution and abundance of some Aquatic Heteroptera to water physico-chemistry from other regions (Savage, 1994;Hufnagel et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous Mediterranean ecosystem assessment studies, and results that identified macroinvertebrate diversity as contributing disproportionately to ecological knowledge for the North African region (Beauchard et al, 2003;Ball et al, 2013;De Figueroa et al, 2013;Slimani et al, 2019). Benthic macroinvertebrates depend on a wide range of abiotic factors, including climate, water physiochemistry, anthropogenic pressures and riparian habitat availability (White et al, 2019;Ceron et al, 2020) and this study confirms that this is also true for aquatic insects such as Heteroptera. This study also supports the finding of research linking the distribution and abundance of some Aquatic Heteroptera to water physico-chemistry from other regions (Savage, 1994;Hufnagel et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, as suggested by our models, the increase in anuran diversity from spring to summer, followed by a decrease through winter, is most likely related to seasonal changes in temperature. Similar cyclic patterns were also observed for other subtropical regions (Bolzan et al, 2019; Ceron et al, 2020). As temperature increases through the summer, higher elevations also become warmer and climatically suitable for larger numbers of species.…”
Section: Discussionsupporting
confidence: 82%
“…Some habitat specialist anuran species (e.g., ground‐dwelling and stream‐dwelling) may have been undersampled. However, previous studies in this region showed that most anuran species found belong to Hylidae, Leptodactylidae and Bufonidae families (~78%–80% of all species; Ceron et al, 2020; Carvalho‐Rocha et al, 2021), which mostly use lentic aquatic environments for reproduction (Haddad et al, 2013; Nunes‐de‐Almeida et al, 2021). Selected ponds spanned elevations between 312 and 1798 m, and were distributed irregularly within this range, but not biased for or against any single elevational band of the gradient (McCain & Grytnes, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Even without a dry season, the subtropical Atlantic Forest present lower temperatures during autumn and winter, with lower precipitation in autumn (Conte and Machado, 2005, Conte and Rossa-Feres, 2007, Santos and Conte, 2014. This evidence Vitreorana uranoscopa reinforces the temperature as the main abiotic factor structuring amphibian communities in subtropical environments (Ceron et al, 2020).…”
Section: Spatial and Temporal Distributionsupporting
confidence: 53%